1973
DOI: 10.1139/m73-222
|View full text |Cite
|
Sign up to set email alerts
|

Improved purification and further characterization of Clostridium perfringens type A enterotoxin

Abstract: The procedure for the purification of Clostridium perfringens type A enterotoxin was simplified, and the purity of the toxin was improved. Hydrolysis of the toxin by the p-toluenesulfonic acid procedure yielded 18 common amino acids. Among these, aspartic acid, serine, leucine, and glutamic acid were the predominant components. The sedimentation coefficient (s°20, w) was 2.8 Svedberg units. The molecular weights determined by the Archibald technique, sedimentation equilibrium, and amino acid analysis were 40 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The amino acid composition of the enterotoxin is given in Table 1. The results are in good agreement with those of Hauschild et al ( 8 ) . The only important significant difference is the result of cysteic acid.…”
Section: Amino Acid Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The amino acid composition of the enterotoxin is given in Table 1. The results are in good agreement with those of Hauschild et al ( 8 ) . The only important significant difference is the result of cysteic acid.…”
Section: Amino Acid Analysissupporting
confidence: 92%
“…The only important significant difference is the result of cysteic acid. In this investigation it was found that the enterotoxin contained only one cysteic acid residue per molecule, compared to two cysteic acids found in the work of Hauschild et al ( 8 ) .…”
Section: Amino Acid Analysismentioning
confidence: 43%
“…Using these data the compositional relatedness was performed between type A (8-6) and type A enterotoxin [18] and type delta toxin [43]. Similar results were obtained using the methods described by Cornish-Bowden [44] and Metzger et al [45].…”
Section: Amino Acid Analysismentioning
confidence: 85%
“…Use of HPLC for gel permeation chromatography and ion-exchange c h r o m a t o g r a p h y in ptace of conventional gel permeation through Sephadex (22,24), ion-exchange c h r o m a t o g r a p h y .on a DEAE (24) .or a QAE-Sephadex column (14), or preparative electrophoresis (8) made the present method rapid and gave high resolution. The conventional methods of c h r o m a t o g r a p h y require at least one day for each step, but in the present HPLC method, one cycle of gel permeation on a G2000SW column and one cycle o.f ion-exchange on a Mono Q column require 50 and 40 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin is produced during sporulation (7,16) and it has been purified (1,8,12,(20)(21)(22)(23)(24)27) from sonic extracts of sporulated bacteria and shown to be a simple protein with a molecular weight of ca. 35000 (11,13,14,25). 1 Corresponding author.…”
Section: Introductionmentioning
confidence: 99%